Clinician perspectives on the need for training on caring for pregnant women with intellectual and developmental disabilities. Issue 2 (April 2022) - Amir, Nili; Smith, Lauren D.; Valentine, Anne M.; Mitra, Monika; Parish, Susan L.; Moore Simas, Tiffany A.
Abstract: Background: Women with intellectual and developmental disabilities (IDDs) experience disparities in obstetric care access and quality, in addition to communication gaps with healthcare providers. Many obstetric providers are untrained and uneducated about critical aspects of providing care to persons with IDDs. Objective: The study was conducted to describe obstetric clinicians' training experiences related to providing obstetric care to women with IDDs, to assess the perceived need for formalized training, and to identify recommendations for training content. Methods: This study involved qualitative individual interviews (n = 9) and one focus group (n = 8) with obstetric clinicians who self-reported experience caring for women with IDDs during pregnancy. Descriptive coding and content analysis techniques were used to develop an iterative codebook related to education and training; codes were applied to the data. Coded data were analyzed for larger themes and relationships. Results: Analysis revealed three main themes: 1. Need for obstetric training and education: No participant reported receiving any training in caring for pregnant women with IDDs. Participants expressed a need for formal education. 2. Recommendations for formal training: Participants noted the need for training during residency and beyond, and all healthcare staff members should be included in training. 3. Training outcomes should increase knowledge, enhance attitudes, and develop practical skills related to care for pregnant women with IDDs. Conclusion: Results indicate a need for systematic training efforts regarding obstetric care for women with IDDs. Improved training and education may decrease health inequities and improve the quality of care, and thus pregnancy outcomes, for women with IDDs. Level of evidence: VI.